Extracellular Vesicle Flow Cytometry Analysis and Standardization - Welsh, Joshua A.; Holloway, Judith A.; Wilkinson, James S.; Englyst, Nicola A. (Frontiers in Cell and Developmental Biology, 2017)
The term extracellular vesicles (EVs) describes membranous vesicles derived from cells, ranging in diameter from 30-1000nm with the majority thought to be in the region of 100-150nm. Due to their small diameter and complex and variable composition, conventional techniques have struggled to accurately count and phenotype EVs. Currently, EV characterisation using high-resolution flow cytometry is the most promising method when compared to other currently available techniques, due to it being a high-throughput, single particle, multi-parameter analysis technique capable of analysing a large range of particle diameters. Whilst high resolution flow cytometry promises detection of the full EV diameter range, standardisation of light scattering and fluorescence data between different flow cytometers remains an problem. In this mini review, we will discuss the advances in high-resolution flow cytometry development and future direction of EV scatter and fluorescence standardisation. Standardisation and therefore reproducibility between research groups and instrumentation is lacking, hindering the validation of EVs use as diagnostic biomarkers and therapeutics.